2005
DOI: 10.1158/0008-5472.can-05-1702
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Expression of Connective Tissue Growth Factor Promotes Angiogenesis and Prostate Cancer Tumorigenesis

Abstract: Our previous studies have defined reactive stroma in human prostate cancer and have developed the differential reactive stroma (DRS) xenograft model to evaluate mechanisms of how reactive stroma promotes carcinoma tumorigenesis. Analysis of several normal human prostate stromal cell lines in the DRS model showed that some rapidly promoted LNCaP prostate carcinoma cell tumorigenesis and others had no effect. These differential effects were due, in part, to elevated angiogenesis and were transforming growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
216
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(225 citation statements)
references
References 47 publications
7
216
0
1
Order By: Relevance
“…Concordantly, TGF-b1 induced smooth muscle a-actin filament formation in TbRII CT control cells; however, TbRII KO cells were refractory to TGF-b-induced filament formation (Figure 1b). Attenuated stromal TGF-b signaling in LNCaP þ stroma xenografts Construction of LNCaP/prostate stromal cell xenografts and evaluation time points followed protocols identical to what we have published previously (Tuxhorn et al, 2002b, c;Yang et al, 2005). Xenografts that were constructed with LNCaP plus TbRII KO stromal cells resulted in a 44.1% decrease in microvessel density (Po0.0001, n ¼ 72 fields from 12 xenografts in each group) and a 49.8% decrease in tumor mass compared to LNCaP plus TbRII CT control stromal cells ( Figure 3a) (Figures 7a and b) with subsequent experiments, Figure 7 shows histology for all xenografts in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Concordantly, TGF-b1 induced smooth muscle a-actin filament formation in TbRII CT control cells; however, TbRII KO cells were refractory to TGF-b-induced filament formation (Figure 1b). Attenuated stromal TGF-b signaling in LNCaP þ stroma xenografts Construction of LNCaP/prostate stromal cell xenografts and evaluation time points followed protocols identical to what we have published previously (Tuxhorn et al, 2002b, c;Yang et al, 2005). Xenografts that were constructed with LNCaP plus TbRII KO stromal cells resulted in a 44.1% decrease in microvessel density (Po0.0001, n ¼ 72 fields from 12 xenografts in each group) and a 49.8% decrease in tumor mass compared to LNCaP plus TbRII CT control stromal cells ( Figure 3a) (Figures 7a and b) with subsequent experiments, Figure 7 shows histology for all xenografts in this study.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that it is highly unlikely that FGF-2 is the only pathway downstream of TGF-b in stroma promoting LNCaP tumor growth, but that it does partially mediate the angiogenic action of TGF-b. In addition to FGF-2, TGF-b stimulates expression of many other growth factors in stromal cells including vascular endothelial growth factor, heparin-binding-epidermal growth factor, interleukin-6 TGF-b signaling in prostate cancer reactive stroma F Yang et al and CTGF (Igarashi et al, 1993;Pertovaara et al, 1994;Story et al, 1996;Uchiyama-Tanaka et al, 2002;Hayashi et al, 2004;Yang et al, 2005), some of which, similar to FGF2, are Smad3 regulated. Hence, focal overexpression of TGF-b at sites of early cancer might be expected to initiate a local reactive stroma, typified by matrix remodeling, induction of myofibroblasts, collagen deposition and induced angiogenesis, similar to the initiation of these events at sites of wound repair, where platelets release TGF-b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Its presence has been shown to be a survival factor for different cell types. 27,28 Previous studies have demonstrated that CTGF may also be a useful therapeutic agent in human rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%